Antiviral Activity of Innate Immune Protein ISG15 - Harty, Ronald N. (S. Karger AG, 2009)
The host innate immune response, including the production of type-I IFN, represents the primary line of defense against invading viral pathogens. Of the hundreds of IFN-stimulated genes (ISGs) discovered to date, ISG15 was one of the first identified and shown to encode a ubiquitin-like protein that functions, in part, as a modifier of protein function. Evidence implicating ISG15 as an innate immune protein with broad-spectrum antiviral activity continues to accumulate rapidly. This review will summarize recent findings on the innate antiviral activity of ISG15, with a focus on the interplay between ubiquitination and ISGylation pathways resulting in modulation of RNA virus assembly/budding. Indeed, ubiquitination is known to be proviral for some RNA viruses, whereas the parallel ISGylation pathway is known to be antiviral. A better understanding of the antiviral activities of ISG15 will enhance our fundamental knowledge of host innate responses to viral pathogens and may provide insight useful for the development of novel therapeutic approaches designed to enhance the immune response against such pathogens.